Performance Evaluation of PPI Dendrimer Based Valsartan and Fenofibrate Formulations. - J. Vijaya Ratna2P.Sureshkumar 1*, N. Hematheerthani1 (Journal of Biomedical and Pharmaceutical Research, 2012)
The purpose of this investigation was to evaluate the performance of poly (propylene imine) (PPI) dendrimers, with three different drug concentrations, to be used as drug carriers. Drug–dendrimers complexes were investigated for dissolution studies, in vitro drug release studies, and for stability studies. The formation of the complexes between drug molecules and dendrimers were characterized by the FTIR, DSC and SEM spectra of these complexes, showing the appearance of the bond formed between the functional groups of the drug (COOH) and dendrimers (NH2). The drug–dendrimer complexes displayed the controlled release action during in vitro release studies. Pure valsartan (VAL) and fenofibrate (FB) was released in 5 h whereas the PPI dendrimers–VAL-FB complexes released the drug up to 24 h. Formulations with PPI dendrimers were subjected to accelerated stability studies and were found to be most stable in dark, low temperature (0°C) whereas the dark, RT was most suitable storage conditions for formulation with PPI dendrimers. KEYWORDS: Dissolution, PPI dendrimer, Valsartan, Fenofibrate